Unity and Contradictions of Modern Interaction of State, Business and Society - I. V. Ganja; R. A. Nabiyev (Путеводитель предпринимателя, 2020)
The article is devoted to the problem of interaction between state and business structures. The concepts of interaction within the triplicity «state-business-society» are preformed. The author also analyses the contradictions and peculiarities of functioning and development of interaction between state and business structures.